Legal Politics of Forming Regional Regulations Based on Local Wisdom in the Era of Digital Transformation of Government - Anies Prima Dewi; Ady Supryadi; Dodi Jaya Wardana (Universitas Muhammadiyah Mataram, 2025)
The digital transformation of government (e-government) has shifted the paradigm of legislative regulation formation, becoming more technocratic and procedurally centralized. This study examines the legal politics of the formation of local wisdom-based Regional Regulations (Perda) in the digital era, focusing on identifying normative conflicts and legal gaps within the national regulatory framework. There are normative gaps in Law Number 12 of 2011 concerning the Formation of Legislation and its amendments, which do not yet regulate the digitalization mechanism for the absorption of unwritten law (customary law) into the legislative information system platform. Furthermore, there is a normative conflict between the principle of legal certainty in the e-Perda digitalization system, which requires standard codification, and the principle of protecting the dynamic, oral, and heterogeneous values of local wisdom. Through a normative juridical approach, this study concludes that current regional legal politics is trapped in digital formalism that reduces the material substance of local wisdom. It is recommended that regional constitutional law be reconstructed through the development of